Trans People, Transitioning, Mental Health, Life and Job Satisfaction - Nick Drydakis (Global Labor Organization (GLO), 2019)
For trans people (i.e. people whose gender is not the same as the sex they were assigned at birth) evidence suggests that transitioning (i.e. the steps a trans person may take to live in the gender with which they identify) positively affects positivity towards life, extraversion, ability to cope with stress, optimism about the future, self-reported health, social relations, self-esteem, body image, enjoyment of tasks, personal performance, job rewards and relations with colleagues. These relationships are found to be positively affected by gender affirmation and support from family members, peers, schools and workplaces, stigma prevention programmes, coping intervention strategies, socioeconomic conditions, anti-discrimination policies, and positive actions. Also important are legislation including the ability to change one's sex on government identification documents without having to undergo sex reassignment surgery, accessible and affordable transitioning resources, hormone therapy, surgical treatments, high-quality surgical techniques, adequate preparation and mental health support before and during transitioning, and proper follow-up care. Societal marginalization, family rejection, violations of human and political rights in health care, employment, housing and legal systems, gendered spaces, and internalization of stigma can negatively affect trans people's well-being and integration in societies. The present study highlights that although transitioning itself can bring well-being adjustments, a transphobic environment may result in adverse well-being outcomes. Policy makers should aim to facilitate transitioning and create cultures of inclusion in different settings, such as schools, workplaces, health services and justice.
Keywords: D91; I10; J12; J10; J28; K38; 330; Trans People; Transitioning; Gender Reassignment Surgery; Mental Health; Life Satisfaction; Job Satisfaction